Emotional Intelligence and Self-Efficacy: Perspectives of Iranian Female EFL Teachers in Building Their Teacher Immunity - Khabazian, Farhad; Kashef , Seyyed Hossein (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Teacher Immunity is one of the essential factors for successful language teaching in educationalcontexts. This study aimed to explore the factors which positively contributed to female EFL teachers’Emotional Intelligence and Self-Efficacy as predictors of their Teacher Immunity in Iranian EFLcontexts. A qualitative interview design was adopted to address the research questions. Furthermore, aconvenience sampling technique was employed to select 15 female EFL instructors from various foreignlanguage institutes in Urmia city. A semi-structural interview questionnaire was used to collect data forthe current study. Additionally, Thematic Data Analysis was employed to extract major themes from thecomments and expressions of the participants. Based on themes emerged from female EFL teachers’comments, self-awareness, effective communication, building a good rapport and conflict managementfactors could positively predict EFL instructors’ teacher immunity. In addition, confidence in teaching,availability of resources and materials, teaching experience and persuasion of instructors were thefactors of female EFL teachers’ self-efficacy which could positively predict their teacher immunity inEFL contexts.